TELAAH FILSAFAT PENDIDIKAN ISLAM DAN IMPLIKASINYA TERHADAP PENDIDIKAN SEUMUR HIDUP MENUJU MASYARAKAT MADANI - Iwan Israwan (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2020)
Civil society in the education aspect is the preparation of human resources with knowledge and civilian behavior through education. It is because the concept of civil society is part of the national education goal. All people may agree that education is important for building human quality, indicated by improving intelligence, knowledge, and skills since education is a strategic sector for the quality of human life by developing in the degree of welfare, a decrease in poverty, and the formation of various options and opportunities to develop themselves towards civil society. The complex problem in lifelong education is faced. Various policies have been made by the Indonesian government. However, in terms of implementation, it is found many obstacles, particularly in the mentality of the people who are lack motivation, so the education cannot be optimized as an institution that has broad community support. Therefore, civil society is important to be reviewed. The research objective is to examine the philosophy of Islamic education as a critical analysis of a philosophical concept, the interpretation of Islamic education, and its implications for lifelong education. The research method used a philosophical approach by seeking a good lesson or wisdom as well as truth. Researchers examined critically that: "Lifelong education is a process of improving personal development, social development, and expertise during the life span of an individual to improve life for both individuals and groups. This is a comprehensive (broad, complete) and integrative (similar, same) idea, which includes informal, formal, and informal learning for expertise and enlightenment to achieve full development at every stage and field of life. This is related to both personal growth and social progress”. In particular, it aims to look more deeply at the philosophical foundations of Islamic education and its implications for the concept of lifelong education towards civil society. Based on this, the conclusion in this paper is that several main bases can be used as a basic building for understanding the nature of Islamic education. The result shows that Islamic Education Philosophy views that education having no purpose that reflects the personality of a nation as what the country will reach will certainly fail. The philosophy of Islamic Education has a strong, strategic, and functional foundation in the effort to build civil society. In this study, the writer examines what kind of educational philosophy is offered by Islam in realizing a civil society.